Back Cover: Phosphono Bisbenzguanidines as Irreversible Dipeptidomimetic Inhibitors and Activity‐Based Probes of Matriptase‐2 (Chem. Eur. J. 25/2016). Issue 25 (23rd May 2016) - Häußler, Daniela; Mangold, Martin; Furtmann, Norbert; Braune, Annett; Blaut, Michael; Bajorath, Jürgen; Stirnberg, Marit; Gütschow, Michael
Abstract : Phosphono bisbenzguanidines as dipeptidomimetic inactivators for matriptase‐2 were discovered. Inhibition of this enzyme is one strategy for the treatment of iron‐overload diseases. Synthetic routes to new inactivators were developed. The irreversible inhibition was kinetically characterized and the binding mode was supported by docking analysis. Based on this chemotype, a fluorescent probe was designed and synthesized. Finally, by applying the first activity‐based probe for matriptase‐2, detection of the target was demonstrated. More information can be found in the Full Paper by M. Gütschow et al. onpage 8525 ff.